Aetiological profile of paediatric stridor in a Malaysian tertiary hospital - S. G., Lum; I., Noor Liza; V., Priatharisiny; A. B., Saraiza; B. S., Goh (Academy of Family Physicians of Malaysia, 2016)
Background: Conditions causing stridor in paediatric patients can range from minor illnesses to life-threatening disorders. Proper evaluation and correct diagnosis are essential for timely intervention. The objective of this study was to determine the aetiological profiles and the management of paediatric patients with stridor referred to the Otorhinolaryngology Department of Hospital Serdang. Methods: Medical records of all paediatric patients presenting with symptom of stridor from January 2010 to February 2015 were reviewed retrospectively. The patients' demographic data, clinical notes, laryngoscope findings, diagnosis and management were retrieved and analysed. Results: Out of the total 137 patients referred for noisy breathing, 121 patients had stridor and were included in this study. There were 73 males and 48 females-most were of Malay ethnicity (77.7%). The age of presentation ranged from newborn to 10 years, with a mean of 4.9 months. Eighteen patients (14.9%) had associated congenital pathologies. The majority were congenital causes (90.9%), in which laryngomalacia was the commonest (78.5%), followed by subglottic stenosis (5.0%), vallecular cyst (2.5%) and congenital vocal fold paralysis (2.5%). Twelve patients (9.9%) had synchronous airway lesion. The majority of the patients were managed conservatively. Thirty-one patients (25.6%) required surgical intervention, of which only one needed tracheostomy. Conclusion: Laryngomalacia was the commonest cause of stridor among paediatric patients. A synchronous airway lesion should be considered if the child has persistent or severe symptoms. The majority of the patients were managed conservatively.